Reinterpreting the Concept of Āsyirūhunna bil Ma‘rūf in QS. An-Nisā’ Verse 19 through the Qira’ah Mubādalah Approach - Adi Harmanto Harahap; Muh. Rizki; Almi Jera (Yayasan Nurul Musthafa, 2025)
The interpretation of the concept ‘āsyirūhunna bil ma‘rūf in QS. An-Nisā’ verse 19 has become increasingly significant in contemporary Islamic discourse, particularly concerning gender justice and marital relations. Classical tafsir traditions tend to interpret this concept within a patriarchal framework, positioning the husband as the dominant figure in the household. This study aims to offer an alternative reading using the Qira’ah Mubādalah approach, which emphasizes reciprocity, equality, and justice in gender relations. Employing a qualitative method based on literature review, this article analyzes classical interpretations such as those by Ibn Kathīr, al-Ṭabarī, and al-Qurṭubī, alongside contemporary perspectives developed by Faqihuddin Abdul Kodir. The findings reveal that the phrase ‘āsyirūhunna bil ma‘rūf is not merely a command for husbands to treat their wives kindly but reflects a principle of mutual and equitable relationship. The Qira’ah Mubādalah approach allows for a more contextual and inclusive reconstruction of this verse’s meaning, making it relevant to the evolving social realities of contemporary Muslim communities. This study contributes to the development of gender-just Qur'anic interpretations and strengthens the paradigm of marital partnership rooted in mutual respect and fairness. [Penafsiran terhadap konsep ‘āsyirūhunna bil ma‘rūf dalam QS. An-Nisā’ ayat 19 menjadi penting dalam diskursus keislaman kontemporer, terutama terkait isu keadilan gender dan relasi suami-istri. Dalam tradisi tafsir klasik, konsep ini cenderung ditafsirkan dalam kerangka patriarkal yang menempatkan suami sebagai figur dominan dalam rumah tangga. Penelitian ini bertujuan untuk menawarkan pembacaan alternatif melalui pendekatan Qira’ah Mubādalah, yang menekankan prinsip kesalingan, kesetaraan, dan keadilan dalam relasi gender. Dengan menggunakan metode kualitatif berbasis studi pustaka, artikel ini menganalisis berbagai tafsir klasik seperti karya Ibn Kathīr, al-Ṭabarī, dan al-Qurṭubī, serta tafsir kontemporer seperti yang dikembangkan oleh Faqihuddin Abdul Kodir. Hasil kajian menunjukkan bahwa frasa ‘āsyirūhunna bil ma‘rūf tidak semata merupakan perintah bagi suami untuk berbuat baik kepada istri, melainkan mencerminkan prinsip relasi timbal balik yang adil dan setara. Penafsiran melalui Qira’ah Mubādalah mampu merekonstruksi makna ayat ini secara lebih kontekstual dan inklusif, serta relevan dengan dinamika sosial masyarakat Muslim saat ini. Temuan ini memberikan kontribusi terhadap pengembangan tafsir berbasis keadilan gender dan memperkuat paradigma relasi pernikahan yang berlandaskan kemitraan.]